Comparative study among the different types of connections in steel building frames - Bing, Chun Chia (2000)
'Steel is one of the most important construction materials today. Its application continues to grow and to diversify, where before buildings were of bricks and mortar today ferroconcrete is the material of choice. In other countries steel-frame buildings are preferred although more expensive, steel-frame buildings are faster to build. A steel industry used to be regarded as the measure of a country's level of development. The more sophisticated the steel industry of a nation, the higher is its level of industrialization. Excerpts of our Prime Minister, YAB. Dato' Seri Dr. Mahathir Mohamad opening address at the Official Opening of the Malaysian Structural Steel Association Convention 2000. This clearly shows that the steel construction has it's very bright future in this country. Tl1e steel consumption is no longer an issue within engineering or steel industry, but it symbolises the level of industrialisation of a country. Our government has stressed the importance of using modem construction practice towards achieving high quality structure. So with all these in mind, steel structures can provide a better choice for the construction industry present needs. Therefore a better understanding of steel structural performance is vital, in order to achieve an optimum and cost balance design. This project is carried out to determine the effect of the choice of the connection types on members' sizes and the economical aspect in the design of a steel structure. STAAD-III analysis and design software is being used to analyse and design for the structure. A release factor, f1 is being introduced for partial moment release use to represent semi-rigid connection behaviour. From this study, it can be concluded that semi-rigid connections achieve the most optimum design in terms of beam section and cost.